Pengukuran Kinerja PT Garuda Indonesia Tbk Berbasis Balanced Scorecard (Performance Measurement of Pt Garuda Indonesia Tbk Based on Balanced Scorecard - Satyodriyani, Kintan Rachmi; Restarani, Hesti; Kaltum, Umi (STIE Malangkucecwara, 2023)
This research aims to analyze the application of the balanced scorecard (BSC) method as a benchmark for measuring performance at PT Garuda Indonesia (Persero) Tbk. This research uses a qualitative descriptive method by analyzing data information that can be measured into research indicators based on the four perspectives of the BSC, financial perspective, customer perspective, internal business perspective and growth and learning perspective. Based on the BSC analysis, in 2018-2021 the company's overall performance was not good. The company's condition is getting better in the 2021-2022 period, marked by an increase in profits and a significant increase in the scores of the four BSC perspectives. This indicates that the company's overall performance is improving compared to previous years